Evaluation Of Peanut Skin Ethanol Extract As Protective Agent Against Lead Acetate Induced Reproductive And Neuromuscular Toxicities In Drosophila Melanogaster - Sani, Hassan; Muhammad, Bawa; Zira, Zaruwa; Bamidele, Titilayo; Lawal, Abdulkadir; Jibrilla, Khadijah; Liman, Jibril (My University, 2023)
Lead acetate exposure is known to cause reproductive and locomotor toxicities in various organisms, including Drosophila melanogaster. This study aimed to assess the ameliorative effects of peanut skin ethanol extract (PSE) against lead acetate-induced toxicities in Drosophila melanogaster. Fly body weight, larval locomotor activity, fecundity, and eclosion activity were evaluated as endpoints. Lead acetate exposure reduced fly body weight, larval locomotor activity, and fecundity, and hindered the eclosion of adult flies. Co-treatment with PSE at different concentrations (LP1, LP2, LP3) further exacerbated these toxic effects, except when co-administered with resveratrol (LR), which mitigated the lead-induced locomotor dysfunction and increased fecundity. Co-treatment with PSE (LP1, LP3) or PSE alone (P1, P2, P3) exceptionally mitigated lead-induced weight loss and increased the fly body weight. Treatment with PSE alone showed a reduction in larval locomotor activity and did not significantly affect fecundity or eclosion. The observed effects may be attributed to the fatty acid content of the peanut skin extract, sensitivity of neuronal pathways, and potential interactions with lead. These findings suggest that peanut skin ethanol extract may have limited protective effects against lead-induced toxicities in Drosophila melanogaster, and further investigations are warranted to understand the underlying mechanisms and potential implications for human health.